2020
DOI: 10.1109/access.2020.3016686
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis and Design of MMC Based on Mission Profile for the Components Degradation

Abstract: In the field of high voltage level applications, modular multi-level converter (MMC) has the definite advantages of low power loss and modularity and there have been many studies on its reliability. Some researches focus on the degradation of physical characteristics in the lifetime prediction of key devices, but the degradation of physical characteristics has not been directly used in the research of MMC system level reliability. The traditional exponential distribution failure rate is constant while the Mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…However, if the number of failed submodules on one arm exceeds the number of redundant submodules, this arm will fail. If any of the arms and converter-level components in the MMC has failed, the converter will fail [23].…”
Section: Failure Mechanism Of Mmcs and Main Steps For Obtaining The P...mentioning
confidence: 99%
“…However, if the number of failed submodules on one arm exceeds the number of redundant submodules, this arm will fail. If any of the arms and converter-level components in the MMC has failed, the converter will fail [23].…”
Section: Failure Mechanism Of Mmcs and Main Steps For Obtaining The P...mentioning
confidence: 99%
“…Based on the data used in several studies [24][25][26], we consider that the typical failure rate of IGBTs is 250 FIT. The average IGBT temperature obtained from figure 11 is about 75 °C, which is common in practical applications [27,28], and the junction temperature can be considered as corresponding to the typical IGBT failure rate value of 250 FIT. The junction temperature fluctuation of IGBTs is 20 °C, which is also within the fluctuation range of usual applications [29].…”
Section: Simulation Verificationmentioning
confidence: 99%
“…They concluded that the reliability of these converters could be improved by selecting appropriate converter topologies and mission profiles. A recent study [ 15 ] has presented an innovative approach for analyzing and designing the reliability of a modular multilevel converter (MMC) system. The proposed method takes into account factors such as IGBT lifetime degradation, mission profile, and thermal network updating methods to optimize redundancy design for better cost trade-off.…”
Section: Introductionmentioning
confidence: 99%